Three-dimensional shape from shading is modulated by top-down attention: Evidence from event-related potentials - Joshua P. Matthews; Debra L. Mills; Ayelet Sapir (i-Perception, 2025)
Shading is an important monocular cue for three-dimensional (3D) perception, whereby 3D shape can be inferred from shading patterns across an object, in a process termed shape-from-shading . Shape-from-shading has been characterised as a pre-attentive process that occurs in parallel across the visual field. Recent evidence, however, has challenged this notion, suggesting that it consists of an early pre-attentive process and a later stage of processing that is reliant on top-down attention. Here, we use event-related potentials (ERPs) to test this claim whilst participants were instructed either to ignore or to attend to shaded stimuli that could be perceived as two-dimensional (2D) and 3D. We found that 3D stimuli evoked a larger N1 component than 2D stimuli in both attended and unattended conditions, implying an early, pre-attentive processing stage in shape-from-shading. This activity was lateralised to the right hemisphere when participants attended to the stimuli, in accordance with the right hemisphere advantage in top-down attention. Further, when participants attended to the stimuli, a larger N2 component for 3D compared to 2D shape was found, suggesting a late, top-down process for identifying 3D shape. These findings provide evidence for two distinct stages of processing for shape-from-shading and suggest that attention is necessary for the perception of shape-from-shading.